2022
DOI: 10.1038/s41598-022-10618-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies loci and candidate genes for grain micronutrients and quality traits in wheat (Triticum aestivum L.)

Abstract: Malnutrition due to micronutrients and protein deficiency is recognized among the major global health issues. Genetic biofortification of wheat is a cost-effective and sustainable strategy to mitigate the global micronutrient and protein malnutrition. Genomic regions governing grain zinc concentration (GZnC), grain iron concentration (GFeC), grain protein content (GPC), test weight (TW), and thousand kernel weight (TKW) were investigated in a set of 184 diverse bread wheat genotypes through genome-wide associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 63 publications
9
44
0
Order By: Relevance
“…The decay of LD was found comparable in the B and D subgenomes (~ 5 cM) compared to the A subgenome, which had a shorter decay distance of around ~ 3 cM. A similar pattern of LD decay was also observed in other GWAS studies in wheat 49,78,79,91 .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The decay of LD was found comparable in the B and D subgenomes (~ 5 cM) compared to the A subgenome, which had a shorter decay distance of around ~ 3 cM. A similar pattern of LD decay was also observed in other GWAS studies in wheat 49,78,79,91 .…”
Section: Discussionsupporting
confidence: 84%
“…The identified MTAs (5) for GFeC on chromosomes 6A, 3B, 1A, 7B, and 5A in this study were novel, as the earlier reported MTAs on the same chromosomes namely 3B, 7B, and 5A 43 , 44 , 1A, 3B, and 5A 23 , 26 , 1A 40 and 6A, 3B 91 were identified at different positions. A total of five novel MTAs was identified for GZnC on chromosome 7B, 6A, 2B, 5B, and 7B.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations